Next Wave of Technology. Issue 2 (2nd April 2016) - Tesar, D.
Abstract: A balanced electro-mechanical system must have the openness now represented by the electricals (computer chips, power boards, standardized interfaces, domain-relevant operational software) and the reconfigurability to not only meet the needs of ever-changing tasks, but also enable rapid assembly, repair, and refreshment on demand by means of highly-certified components made available by means of a competitive supply chain. This, then, requires a command/response in milli-sec for multi-input/multi-output (MIMO) systems that are normally perceived as highly non-linear and highly coupled (i.e., unsolvable by standard analytic tools). Criteria-based decisions in milli-sec essentially linearize these systems to make strictly algebraic processes viable with little or no uncertainty so long as the operational criteria have clear physical meanings. The human command (trains, surgery, aircraft, automobiles, etc.) in concert with semi-autonomous processes can be put into balance where each plays its relevant role. The missing ingredient in this accelerated development of the tech base for the mechanicals is the intelligent actuator (i.e., the action part of the full physical system) as the computer chip is to the electrical system.